Criticism of criticism of modernists - دهيكيل, محمد علي سليمان (Tobruk University Journal of Social and Human Sciences, 2024)
This study deals with the criticism of criticism in samples of the poetry of modern poets, in order to reveal the features and aspects of this criticism.   Criticism is a persuasive argumentative reading that addresses creativity, and criticism of criticism is reading upon reading. Arguments and persuasion plead for criticism in its discourse, and it relies on description. It cannot be claimed that all criticism is unsound due to the reasons for issuance or error in the readings. In this research, entitled (Critique of Criticism among Modernists), I dealt with the role of some poets, critics, and writers in criticism of criticism, and poetic models of criticism of criticism between some poets and critics, such as criticism of criticism. betweenAli Al-Jundi and Hafez Ibrahim, and between Ahmed Shawky and Ali Al-Jarem, and between Al-Akkad and Ali Al-Jarim and Ahmed Abdel-Moati Hijazi, and between Mahmoud Ghoneim and Omda Adeeb and Ahmed Kamal Zaki. This term appeared in the world of literature in the twentieth century in Arab and Western literature. I showed in these models the criticism of criticism of these poets and writers. This is what made criticism itself a subject of reflection and analysis.